2003
DOI: 10.1007/s10353-003-0027-6
|View full text |Cite
|
Sign up to set email alerts
|

Watertightness and Effectiveness of a Fibrinogen-Based Collagen Fleece (TachoComb®) in Neurosurgery

Abstract: Background: Meningitis or cerebrospinal fluid rhinorrhoea can occur years or even decades after trauma or operation and can be the first indication of a previously unidentified dural lesion. Preventing cerebrospinal fluid (CSF) leakage with a fibrinogen-based collagen fleece (TachoComb ® ) was the interest of our clinical study. Methods: In the present study, we examined the watertightness and effectiveness of TachoComb ® following supratentorial/infratentorial as well as skull-base operations. The dura was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The operations were performed on various organs, such as the liver, vascular system, heart, spleen, thorax, and kidney, and the results supported the effi cacy and safety of TachoSil as a hemostatic agent. TachoComb ® has been used as a dural substitute, and a clinical study of 288 patients revealed no superfi cial or deep wound infections or aseptic meningitis [ 24 ] .…”
Section: Fibrin Glue Sheetmentioning
confidence: 99%
“…The operations were performed on various organs, such as the liver, vascular system, heart, spleen, thorax, and kidney, and the results supported the effi cacy and safety of TachoSil as a hemostatic agent. TachoComb ® has been used as a dural substitute, and a clinical study of 288 patients revealed no superfi cial or deep wound infections or aseptic meningitis [ 24 ] .…”
Section: Fibrin Glue Sheetmentioning
confidence: 99%
“…Thus, a combination of collagen and FS is effective, safe and biocompatible. No further adverse events, complications or toxicity were reported [ 14 16 , 28 , 29 ].…”
Section: Brainmentioning
confidence: 99%
“…Therefore, all donors were carefully selected. Although no undesirable effects caused by the fibrinogen-based collagen sponge Tachocomb have occurred until now, the possibility of hypersensitivity and allergic or anaphylactic reactions cannot be excluded completely [13,14,15]. However, it is reported that collagen-based heterologous products have a double advantage: the first one is that it does not initiate an inflammatory response or a foreign body reaction and the second is that the collagen fiber network acts as a matrix for endogenous neodura growth [16,17].…”
Section: Discussionmentioning
confidence: 99%